Miejska przestrzeń pamięci (na podstawie wybranych utworów Herkusa Kunčiusa, Ričardasa Gavelisa, Grigorija Kanowicza) - Krupowies, Walentyna (Studia Rossica Posnaniensia, 2024)
This article analyses literary representations of Vilnius as a Central and Eastern European city, whose space becomes the field where the memory of many national traditions can be observed. The analysis was conducted on the basis of two novels by Lithuanian writers, i.e. A Lithuanian in Vilnius by Herkus Kunčius and A Vilnius poker by Ričardas Gavelis, as well as the works of Grigory Kanovich, a Lithuanian-Jewish author writing in Russian, i.e. the novel The park of forgotten Jews and the autobiographical-memoir prose Dream about vanished Jerusalem. The conflict-generating aspect of memory is revealed in the works of Lithuanian writers. The city centre becomes a battlefield for the commemoration of one’s own tradition and a sphere of action against the tradition of the Other, consisting of concealing, marginalising, and removing. Kanovich’s works focus on the issue of Jewish memory in Vilnius after the Holocaust, when the ghetto ceased to exist. Memory becomes present when literary heroes look back at their past. They meet in the park to revive it together. The narration allows us to see how one of the oldest parks in Vilnius is transformed into a Jewish memorial site.